The Effect of Safety Signs on the Monitoring of Conflict and Erroneous Response - Hu, Linfeng; Feng, Dingzhong; Li, Yelang; Xu, Jinwu; Zheng, Jiehui (Frontiers in Psychology, 2022)
The safety sign is important in our daily life and workplace to prevent potential safety issues. However, it remains undetermined whether the safety signs would influence the cognitive control ability of the people, which serves to guide the behaviors in a goal-directed manner. Therefore, this study aimed to examine the effect of safety signs on cognitive control by uncovering the behavioral performance and neural manifestations underlying the monitoring of conflict and error. The participants performed a flanker task after watching low- and high-hazard safety signs with EEG data recorded continually. The behavioral results indicated a classic congruency effect with higher accuracy rate and faster response time under congruent condition compared to incongruent condition. However, no hazard effect on behavioral performances was observed. The ERPs results demonstrated a more negative N2 elicited by the incongruent trials and increased ERN difference between error and correct responses in the high-hazard condition compared to those in the low-hazard condition, implying that the monitoring of the conflict and error were both enhanced after watching the high-hazard safety signs. This study contributes to the understanding of the relationship between safety signs and cognitive control, and further expand the measurements that can be applied to assess the effectiveness of safety signs design.